How Can We Live Together? - Rikhotso, Rhulani (School of Architecture, Planning and Geomatics, 2024)
The research aims to explore an informal settlement called Hopefield (commonly known as “Kapok”) in Ennerdale. It has been a point of inquiry that sees a need for infrastructural development as well as social engagement to fulfil the idea of a self-sustaining community. The outcomes for the research are that of socio-economic improvement strategies, skilled labour utilisation, and cultural awareness to shift negative narratives associated with Kapok to build upon the positive spatial and sociology-economic strategies that exist within the informal settlement. This intervention has been a lingering thought since my childhood, seeing that I had spent equal time in both formal and informal parts of Ennerdale. It is worth exploring, with the knowledge of South Africa's oppressive history in pinpointing how it has shaped the issues that are prevalent in Ennerdale today, just as much as they are also prevalent in most townships across South Africa.